Analysis of Crop Rotation and Compost Use on Organic Carrot Production Results in Rejang Lebong Regency - Reko Apriantonedi; Halim Ma'shum; Haryuni Haryuni; Rizky Septika Utami; Eko Fransisko (West Science Interdisciplinary Studies, 2025)
This study investigates the impact of crop rotation and compost use on organic carrot production yield in Rejang Lebong District. Using a quantitative approach, data were collected from 60 organic carrot farmers through a structured questionnaire with a Likert scale (1–5). The data were analyzed using SPSS version 25 to examine the effects of these practices on yield. The findings reveal that both crop rotation and compost use have significant positive effects on organic carrot yields, with compost use showing the strongest influence. A synergistic effect was observed when both practices were combined, leading to improved soil health, nutrient availability, and pest management. The study highlights the importance of integrating sustainable agricultural practices to optimize organic carrot production. These insights are valuable for farmers, policymakers, and agricultural stakeholders aiming to enhance productivity while maintaining sustainability.